2020
DOI: 10.5539/jel.v9n1p144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Exercises on Body Composition and Some Biochemical Parameters

Abstract: Exercise has many positive effects on the human organism. In this study, the effects of resistance exercise program, which is applied regularly for eight weeks, were investigated on body composition and some biochemical values. Twenty-four male volunteers participated in the study group. The participants were randomly divided into two equal groups: control and resistance exercise groups. While the participants in the control group attended only practice lessons in the faculty, the exercise group participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In another study conducted by de Moraes et al (2018), it was reported that training and Nacetylcysteine (NAC) supplement caused changes in ALT, AST, LDH, ALP, CK and some biochemical parameters, indicators of cell damage and oxidative stress in volleyball players, and N-acetylcysteine (NAC) provided with training would decrease oxidant effect [27]. Akbulut [28] expressed that eight weeks of resistance exercises had important effects on liver enzymes and body composition of participants. Uadia et al [29] argued that a six-week training program did not lead to any change in liver enzymes and some biochemical parameters of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted by de Moraes et al (2018), it was reported that training and Nacetylcysteine (NAC) supplement caused changes in ALT, AST, LDH, ALP, CK and some biochemical parameters, indicators of cell damage and oxidative stress in volleyball players, and N-acetylcysteine (NAC) provided with training would decrease oxidant effect [27]. Akbulut [28] expressed that eight weeks of resistance exercises had important effects on liver enzymes and body composition of participants. Uadia et al [29] argued that a six-week training program did not lead to any change in liver enzymes and some biochemical parameters of the participants.…”
Section: Discussionmentioning
confidence: 99%